Quality Valuation of a Novel Dual Stator Dual Rotor U-Shaped Permanent Magnet Synchronous Generator for Nuclear Energy Extraction - Kumar R.R.; Paul R.; Sarma J.; Kumari A.; Chetri C.; Saket R.K.; Padmanaban S.; Leonowicz Z. (My University, 2025)
The key goal of the paper is to assess the performance of a Novel Dual Stator Dual Rotor Six-Phase U-Shaped Permanent Magnet Synchronous Generator (NDSDRSPUS-PMSG) that can be used in nuclear energy extraction. In nuclear power plants, synchronous generators are currently used to produce electricity. A feasible alternative is to use a compact-sized high power density Permanent Magnet Synchronous Generator (PMSG). The topology having two rotors-stator provides better power density, and the use of U-shape makes the magnet stronger by pointing the poles flux in the same direction. With greater torque density, higher durability, smaller size and robustness, the multiphase system surpasses the conventional 3-phase system. The output parameters like developed Electromotive Force (EMF), output power, ripple torque, losses, efficiency, total harmonic distortion (THD), and voltage regulation is calculated using Finite Element Method (FEM) for the proposed generator along with comparison with Dual Stator-Rotor Six-Phase Surface Mounted Permanent Magnet Synchronous Generator (DSDRSPSM-PMSG). It is deduced from the comparative review that the NDSDRSPUS-PMSG outperforms the competition, making it more reliable and efficient in the long run. © 2021 IEEE